Conservative Nonhormonal Options for the Treatment of Male Infertility: Antibiotics, Anti-Inflammatory Drugs, and Antioxidants. (9th January 2017) - Calogero, Aldo E.; Condorelli, Rosita A.; Russo, Giorgio Ivan; La Vignera, Sandro
Abstract : The nonhormonal medical treatment can be divided into empirical, when the cause has not been identified, and nonempirical, if the pathogenic mechanism causing male infertility can be solved or ameliorated. The empirical nonhormonal medical treatment has been proposed for patients with idiopathic or noncurable oligoasthenoteratozoospermia and for normozoospermic infertile patients. Anti-inflammatory, fibrinolytic, and antioxidant compounds, oligo elements, and vitamin supplementation may be prescribed. Infection, inflammation, and/or increased oxidative stress often require a specific treatment with antibiotics, anti-inflammatory drugs, and/or antioxidants. Combined therapies can contribute to improve sperm quality.